Light and Colour - Dixon Malcolm (Evans Brothers Limited, 1997)
In this book children's ideas about light and colour are developed through a combination of simple text, beautiful photographs and fun-t0-d0 activities. By experimenting with mirrors, making shadows,finding camouflage and mixing colours, young children will begin to realise how important light and colour are in their lives.
Keywords: Non Fiction / Science / Light and colour